Pulmonary synovial sarcoma - Gupta, Ankit (Respir Med Case Rep, 2018)
Primary Synovial sarcoma of the lung is an extremely rare entity. Our patient was healthy prior to presentation and came in with a short course of dyspnea and was found to have a large synovial sarcoma on the lung.